EFFECT OF ESSENTIAL OILS OF GARLIC, CLOVE AND CINNAMON ON ESCHERICHIA COLI IN CHICKEN MEAT NUGGETS - A. Jagadeesh Babu; D.Maheswara Reddy; B. Eswara Rao (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Chicken meat nuggets were treated with essential oils of g hat essential oils of garlic in treatment groups ( T1 and T2 ) reduced the counts up to day 2 of storage afterwards there was a gradual increase in counts. Coliform count in chicken meat nuggets with essential oils of clove and cinnamon revealed that even though there was a progressive increase in counts up to day 14 of storage they were less in number when compared to the counts on day 0 of storage.